Socio-economic Correlates of Body Mass Index, Blood Pressure and Contraceptive Use by Reproductive age-group Females - Sinha, Richa; Maheshwari, Sonam; Gupta, Puneet; Roy, Debabrata; Deepshikha, . (Indian Journal of Community Health, 2022)
Background: Oral Contraceptive use, BP and BMI are strongly associated variables in terms of socio economic conditions. Oral Contraceptives are an important and widely accepted contraceptive modality used throughout the world. Aim & Objective: This study aims to examine the effects of socio-economic factors on Body Mass Index (BMI), Blood pressure (BP) and contraceptive use by reproductive age-group females of Uttarakhand. Settings and Design: This study utilizes nationwide data from the Fourth National Family Health Survey (NFHS-IV). Methods and Material: Information was collected from Indian Institute of Population Sciences (IIPS) Mumbai and 17,300 women of Uttarakhand were considered for this study. Statistical analysis used: For inter age-group comparisons of blood pressure, BMI and socio-demographic indicators, analysis of variance (ANOVA) technique has been used. Results: The variation in mean age at menarche was found to be significant (p< 0.01, ANOVA). The numbers of live births over the women's total lifetime were lower in the younger age groups (p<0.01, ANOVA). Conclusions: The important findings of present study were that the use of contraceptive tended to have increased BMI and elevated blood pressure, even though the magnitude of these was little (equal to 4% and 40% respectively).